Asking New Questions with Old Data: The Centralized Open-Access Rehabilitation Database for Stroke - Lohse, Keith R.; Schaefer, Sydney Y.; Raikes, Adam C.; Boyd, Lara A.; Lang, Catherine E. (Frontiers in Neurology, 2016)
Background: This paper introduces a tool for streamlining data integration in rehabilitation science, the Centralized Open-Access Rehabilitation database for Stroke (SCOAR), which allows researchers to quickly visualize relationships among variables, efficiently share data, generate hypotheses, and enhance clinical trial design. Methods: Bibliographic databases were searched according to inclusion criteria leaving 2,892 titles that were further screened to 514 manuscripts to be screened by full text, leaving 215 randomized controlled trials in the database (489 independent groups representing 12,847 patients). Demographic, methodological, and statistical data were extracted by independent coders and entered into SCOAR. Results: Trial data came from 114 locations in 27 different countries and represented patients with a wide range of ages, 62 yr [41; 85], (shown as median [range]) and at various stages of recovery following their stroke, 141 d [1; 3372]. There was considerable variation in the dose of therapy that patients received, 20 h [0; 221], over interventions of different durations, 28 d [10; 365]. There was also a lack of common data elements (CDEs) across trials, but this lack of CDEs was most pronounced for baseline assessments of patient impairment and severity of stroke. Conclusions: Data integration across hundreds of RCTs allows clinicians and researchers to quickly visualize data from the history of the field and lays the foundation for making SCOAR a living database to which researchers can upload new data as trial results are published. SCOAR is a useful tool for clinicians and researchers that will facilitate data visualization, data sharing, the finding of relevant past studies, and the design of clinical trials by enabling more accurate and comprehensive power analyses. Furthermore, these data speak to the need for CDEs specific to stroke rehabilitation in randomized controlled trials. PROSPERO# CRD4201409010